2005
DOI: 10.1111/j.1740-0929.2005.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of selected grasses in North Sumatra, Indonesia

Abstract: The nutritive values of seven native grass species collected in North Sumatra, Indonesia, during dry and rainy seasons were evaluated. The chemical composition, in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), in vitro crude protein digestibility (IVCPD), macro mineral concentrations of calcium, phosphorus and magnesium, in vitro gas production profile and metabolizable energy (ME) content of the grasses varied greatly among species and seasons. The crude protein conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
3
3
1
Order By: Relevance
“…The CP of indigenous Brachiaria was similar to the results found by Enoh et al (2005) who reported that CP level in B. decumbens after twelve weeks (three months) of harvest was of 5.8% in Adamawa plateau of Cameroon. Nevertheless, our results on CP of the indigenous Brachiaria were lower than that found by Evitayani et al (2005). They stated that in the tropical region of Indonesia, Brachiaria decumbens collected in the natural grassland of Sumatra during the wet and dry seasons, CP was 12.8 and 8.7%, respectively.…”
Section: Quality Of Tested Grassescontrasting
confidence: 89%
See 1 more Smart Citation
“…The CP of indigenous Brachiaria was similar to the results found by Enoh et al (2005) who reported that CP level in B. decumbens after twelve weeks (three months) of harvest was of 5.8% in Adamawa plateau of Cameroon. Nevertheless, our results on CP of the indigenous Brachiaria were lower than that found by Evitayani et al (2005). They stated that in the tropical region of Indonesia, Brachiaria decumbens collected in the natural grassland of Sumatra during the wet and dry seasons, CP was 12.8 and 8.7%, respectively.…”
Section: Quality Of Tested Grassescontrasting
confidence: 89%
“…The P of local Brachiaria (control) in both seasons was less than that of Prezotto et al (2005) who recorded P value of 0.91% in B. decumbens during the second cut. However, it was Mutimura and Everson 151 similar to that of Evitayani et al (2005) who recorded (0.19 and 0.21%) during the dry and wet seasons respectively in Indonesia. In the wet season, the P content in cv.…”
Section: Quality Of Tested Grassessupporting
confidence: 64%
“…The CP content of the hay from A. gayanus was comparable to the values of 87 and 102 g/kg DM found by Evitayani et al (2005) and Phengvichith and Ledin (2007), respectively, but was higher than the 57 g/kg DM reported by Kaboré-Zoungrana et al (1999). The hay was harvested at early maturity, which may explain the, for tropical grasses, relatively high CP content.…”
Section: Feed and Nutrient Intakesupporting
confidence: 89%
“…The model simulates Guinea grass growth using the APSIM Bambatsi module (Panicum coloratum var. makarikariense) with modifications to the configuration settings for target nitrogen con centrations for leaf (0.017 kg kg �1 ) and stem (0.012 kg kg �1 ) (based on Bamikole et al, 2004;Brâncio et al, 2003;Evitayani et al, 2005;Perissato-Cano et al, 2004). The model contains APSIM manager statements (Table 2) constructed to simulate Guinea grass produc tion with necessary linkages with other model components.…”
Section: Guinea Grass Simulation In Apsimmentioning
confidence: 99%